On Weighted $L^p$-Approximation by Weighted Bernstein-Durrmeyer Operators (Analysis in Theory and Applications, 2018)
In the present paper, we establish direct and converse theorems for weightedBernstein-Durrmeyer operators under weighted $L^p$−norm with Jacobi weight $w(x) = x^{α}(1−x)^{β}$. All the results involved have no restriction $α$, $β
Keywords: Weighted $L^p$−approximation; weighted Bernstein-Durrmeyer operators; direct and converse theorems.